Outline of Real Physics (Global Journal of Science Frontier Research, 2020)
Real physics is an axiomatic theoretical system based on the model of elastic particles. Unlike point-like and wave-like particles, elastic particles are objects with both mass and volume, which can spin and deform. Electrons, protons, and atoms are elastic particles. Elastic particles have three motion modes of translation, rotation, and vibration. The system of elastic particles follows simple and universal laws of motion. This paper briefly reviews the core concepts, basic principles, main contents, and major achievements of real physics. It shows that the classical physical laws (laws of motion, gravitation, electromagnetism, and thermodynamics) are all conclusions drawn from the statistics of elastic particles, which reveals the irreversibility of natural processes.
Keywords: particle; interaction; the unified field; the essence of quantum; laws of physics